The Autoimmune Disorder Susceptibility Gene CLEC16A Restrains NK Cell Function in YTS NK Cell Line and Clec16a Knockout Mice - Pandey, Rahul; Bakay, Marina; Hain, Heather S.; Strenkowski, Bryan; Yermakova, Anastasiya; Kushner, Jake A.; Orange, Jordan S.; Hakonarson, Hakon (Frontiers in Immunology, 2019)
CLEC16A locus polymorphisms have been associated with several autoimmune diseases. We overexpressed CLEC16A in YTS natural killer (NK) cells and observed reduced NK cell cytotoxicity and IFN-γ release, delayed dendritic cell (DC) maturation, decreased conjugate formation, cell-surface receptor downregulation and increased autophagy. In contrast, siRNA mediated knockdown resulted in increased NK cell cytotoxicity, reversal of receptor expression and disrupted mitophagy. Subcellular localization studies demonstrated that CLEC16A is a cytosolic protein that associates with Vps16A, a subunit of class C Vps-HOPS complex, and modulates receptor expression via autophagy. Clec16a knockout (KO) in mice resulted in altered immune cell populations, increased splenic NK cell cytotoxicity, imbalance of dendritic cell subsets, altered receptor expression, upregulated cytokine and chemokine secretion. Taken together, our findings indicate that CLEC16A restrains secretory functions including cytokine release and cytotoxicity and that a delicate balance of CLEC16A is needed for NK cell function and homeostasis.